Women's Linguistic Features in Two Dramas (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
The present paper aims at describing linguistic features of two women who have two different characteristics ” feminine and less feminine” as apparent in Who's Afraid of Virginia Woolf and The Lover dramas. Using Robin Lakoff's (1975) women's linguistic features, the research found out that not all features occur in the dialogues of the two female characters with other characters. Nine features were applied by Martha in Who's Afraid of Virginia Woolf drama and seven features were used by Sarah in The Lover. Based on the analysis of the data, it is uncovered that the use of the women's linguistic features reflects uncertainty and lacking confidence on the part of the women in their conversation.